2011
DOI: 10.1038/mp.2011.159
|View full text |Cite
|
Sign up to set email alerts
|

5-HT2B receptors are required for serotonin-selective antidepressant actions

Abstract: The therapeutic effects induced by serotonin-selective reuptake inhibitor (SSRI) antidepressants are initially triggered by blocking the serotonin transporter and rely on long-term adaptations of pre- and post-synaptic receptors. We show here that long-term behavioral and neurogenic SSRI effects are abolished after either genetic or pharmacological inactivation of 5-HT(2B) receptors. Conversely, direct agonist stimulation of 5-HT(2B) receptors induces an SSRI-like response in behavioral and neurogenic assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
165
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(177 citation statements)
references
References 39 publications
11
165
1
Order By: Relevance
“…Despite these parallels, our current results cannot exclude that at least part of the effects of Htr2b ablation are caused by its expression in other cell types. Besides mononuclear phagocytes, Htr2b is expressed at detectable levels in serotonergic neurons themselves [16], and is known to regulate serotonin release [2,17]. It is therefore possible that the observed decrease in weight in SOD1(G86R) mice devoid of the Htr2b gene was due to serotonergic neurons indirectly affecting hypothalamic circuitry, consistent with our recent results (Vercruysse et al,…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite these parallels, our current results cannot exclude that at least part of the effects of Htr2b ablation are caused by its expression in other cell types. Besides mononuclear phagocytes, Htr2b is expressed at detectable levels in serotonergic neurons themselves [16], and is known to regulate serotonin release [2,17]. It is therefore possible that the observed decrease in weight in SOD1(G86R) mice devoid of the Htr2b gene was due to serotonergic neurons indirectly affecting hypothalamic circuitry, consistent with our recent results (Vercruysse et al,…”
Section: Discussionsupporting
confidence: 82%
“…5-HT 2B R is expressed in microglia in the CNS [40], with expression in other cell types including brain serotonin neurons [16]. In human peripheral macrophages, 5-HT 2B R mediates the response to serotonin by skewing macrophages to a M2, anti-inflammatory, phenotype [14].…”
Section: Introductionmentioning
confidence: 99%
“…The uninjured right femoral arteries served as negative controls. For investigating the effect of 5‐HT2BR agonist BW723C86 on restenosis, mice underwent femoral wire injury and received a pluronic gel (30%) with or without BW723C86 (10 mg/kg),32, 33 which was applied to the external surface of the injured femoral artery. Three days to 4 weeks after surgery, the femoral arteries were harvested, embedded in paraffin wax, and cut into 5‐μm sections for hematoxylin and eosin and Masson staining (Service Biological Technology, Wuhan, China), then observed using a light microscope (Leica DM3000B).…”
Section: Methodsmentioning
confidence: 99%
“…The neurotransmitter GABA was found to depolarize and promotes the differentiation of NPCs [36]. Serotonin, which is originally associated with depressive disorder, is another neurotransmitter which regulates neurogenesis [37]. Direct stimulation of serotonin receptor 5HT(2B) promotes neurogenesis while inactivation of the receptor abolished the neurogenic and therapeutic effect of SSRI.…”
Section: Neurogenesis and Depressive Disordermentioning
confidence: 99%
“…Though some other controversial results have also shown, these results have given the possible relationship between the morphological changes of the amygdala and the pathophysiologic development of autism. Mercadante et al [99] [110,111] Growth factors: 1) Brain-derived neurotrophic factor (BDNF) [31] 2) Vascular endothelial growth factor (VEGF) [41] 3) Insulin-like growth factor 1 (IGF1) [41] Neurotransmitters: 1) GABA [36] 2) Serotonin [37] 3) Glutamate/NMDA receptor [38] 4) Dopamine and acetylcholine [39] -Decrease in number of Ki-67 +ve cells in schizophrenia patients [26] Intracellular molecules: 1) Disrupted in Schizophrenia 1 (DISC1) [75] 2) Neuronal PAS domain protein 3 (NPAS3) [85] 3) Neuregulin 1 (NRG1) [ [99,103] have further suggested that the new immature-neurons newly produced in the amygdala may be helpful in increasing the ability to learn from new experiences via modulation of the gamma-aminobutyric acid (GABA) as patients with autism were found to have alteration on the GABAergic system. However, further investigations are needed as this is a new etiologic hypothesis of autism.…”
Section: Amygdala and Cortex: Non-traditional Neurogenic Regions Andmentioning
confidence: 99%